2011
DOI: 10.1099/jmm.0.025056-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of enterovirus 71 and coxsackievirus A16 using the 5′ untranslated region and VP1 region

Abstract: Enterovirus 71 (EV71) and coxsackievirus A16 (CVA16) are members of the species Human enterovirus A, and are both major and independent aetiological agents of hand-foot-and-mouth disease. The human enterovirus (HEV) 59 untranslated region (UTR) is fundamentally important for efficient virus replication and for virulence, whilst the VP1 region correlates well with antigenic typing by neutralization, and can be used for virus identification and evolutionary studies. A comparison was undertaken of the 59UTR and V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…41,42 The nucleotide variety between genotype B1 and B2 was 11.8%. 41 Genotypes B1a and B1b were the predominant circulating genotypes in Australia from 1999 to 2006, 43 and genotype B circulated in Malaysia from 1997-2006. 44 Phylogenetic analysis of CA16 isolated from 6 provinces in Mainland China from 1995 to 2008 showed that these strains were mainly subtypes B1a and B1b.…”
Section: Molecular Epidemiology Of Ca16mentioning
confidence: 99%
See 1 more Smart Citation
“…41,42 The nucleotide variety between genotype B1 and B2 was 11.8%. 41 Genotypes B1a and B1b were the predominant circulating genotypes in Australia from 1999 to 2006, 43 and genotype B circulated in Malaysia from 1997-2006. 44 Phylogenetic analysis of CA16 isolated from 6 provinces in Mainland China from 1995 to 2008 showed that these strains were mainly subtypes B1a and B1b.…”
Section: Molecular Epidemiology Of Ca16mentioning
confidence: 99%
“…41,42 Therefore, more information on the molecular characterization of CA16 should be provided and a standard genotyping method basing on the VP1 nucleotide sequence should be established to properly study the molecular epidemiology of CA16. [42][43][44] Evolutionary rate analysis was performed using the sequence of VP1, and it was found that the annual evolution rate of CA16 was 0.91 × 10 -2 substitutions per synonymous nucleotide/year, 41 slightly lower than that of EV71 at 1.35 × 10 -2 . 45 A growing body of evidence supports the existence of recombination events involving EV71 and various HEV-A, including CA16 and CA8.…”
Section: Molecular Epidemiology Of Ca16mentioning
confidence: 99%
“…Based on the analysis of different biological features of G20-D and G20-M and according to the basic principles of biological characteristics and related gene sequences of enteroviruses [19][20][21], we decided to sequence the 5′-noncoding region, the 3′ non-coding region, and the VP1 coding region. We repeated the sequencing three times and aligned the sequence ( Figure 4A).…”
Section: Comparison Of Gene Sequences Of the Two Phenotypically Diffementioning
confidence: 99%
“…PV2 EU566945-SPA-? PV2 EU566948- PCR primers and sequencing primers for 5' UTR and VP1: published primers for PCR amplification (5UTR-S and 5UTR-A1) and sequencing (5UTR-S and 5UTR-A2) of partial 5' UTR were used [15]. Published primers 494 to 497 for PCR amplification and sequencing of complete VP1 were obtained [16], as well as PCR amplification and sequencing primers 292 and 222 for analysis of partial VP1 sequences [16].…”
Section: Methodsmentioning
confidence: 99%
“…Reverse transcription (RT) was performed as described previously [17]. EV-specific 5' UTR PCR (using primers 5UTR-S and 5UTR-A1) for all 16 EV local isolates and partial VP1 PCR (using primers 292 and 222) for four isolates were performed as described previously [15]. The methods of complete VP1 PCR for 12 EV-C isolates were as described previously [17].…”
Section: Methodsmentioning
confidence: 99%